Are there adverse consequences of quizzing during informed consent for HIV research? - J. Sugarman (2018)
Introduction: While quizzing during informed consent for research to ensure understanding has become commonplace, it is unclear whether the quizzing itself is problematic for potential participants. In this study, we address this issue in a multinational HIV prevention research trial enrolling injection drug users in China and Thailand. Methods: Enrolment procedures included an informed consent comprehension quiz. An informed consent survey followed. Results: 525 participants completed the informed consent survey (Heng County, China=255, Xinjiang, China=229, Chiang Mai, Thailand=41). Mean age was 33 and mean educational level was 8 yrs. While quizzing was felt to be a good way to determine if a person understands the nature of clinical trial participation (97%) and participants did not generally find the quiz to be problematic, minorities of respondents felt pressured (6%); anxious (5%); bored (5%); minded (5%); and did not find the questions easy (13%). In multivariate analysis, lower educational level was associated with not minding the quizzing (6e10 yrs vs 0e5 yrs: OR=0.27, p=0.03; more than 11 yrs vs 0e5 yrs: OR=0.18, p=0.03). There were also site differences (Heng County vs Xinjiang) in feeling anxious (OR=0.07; p=<0.01), not minding (OR=0.26; p=0.03), being bored (OR=0.25; p=0.01) and not finding the questions easy (OR=0.10; p=<0.01). Conclusions: Quizzing during the informed consent process can be problematic for a minority of participants. These problems may be associated with the setting in which research takes place and educational level. Further research is needed to develop, test and implement alternative methods of ensuring comprehension of informed consent.